PERAN ISTRI NELAYAN DALAM PENINGKATAN EKONOMI RUMAH TANGGA PESISIR DI DESA BRANTA PESISIR KECAMATAN TLANAKAN KABUPATEN PAMEKASAN - Fahrul Anang; Endang Tri Wahyurini; Doni Ferdiansyah (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2022)
Fishermen's wives are able to provide for the daily requirements of their families by working as family members. Quantitative research is used here. on the findings of a straightforward regression test. The t table in this study is known to be 0.67874 for degrees of freedom df 60-2 = 58 with a significance level of 0.05. The table above shows the t value of 6.034 for the variable of economic improvement. because (6.034>0.67874) in the t count t table. Based on the findings, the R2/RSquare coefficient of determination is 0.386, or 38.6%. The impact of economic growth on the function of fishermen's wives is 66.2 percent, or 0.662 percent, in magnitude. A joint/simultaneous test is also part of this investigation. The f test can be used to perform this joint test. It can be deduced from this f test that the significance level is 0.000> 0.05 and the calculated F value is 36,412 f table 4,007 that the t test and the f Ha test are accepted and Ho is rejected, indicating that the role of the fisherman's wife has a significant impact on the variable of increasing the home economy. stairway to success in Tlanakan District, Pamekasan Regency's Branta Pesisir Village.